Probable Hydrochlorothiazide-Induced Myopericarditis: First Case Reported - Toufik Mahfood Haddad; Muhammad Sarfraz Nawaz; Ahmed S. Abuzaid; Smrithy Upadhyay; Pallavi Bellamkonda; Aryan N. Mooss (Case Reports in Medicine)
Hydrochlorothiazide has never been reported as a reason for myopericarditis. An African American female, with past history of hypertension, coronary artery disease, and sulfa allergy, presented with indolent onset and retrosternal chest pain which was positional, pleuritic, and unresponsive to sublingual nitroglycerin. Her medications included hydrochlorothiazide (HCTZ) which was started three months ago for uncontrolled hypertension. Significant laboratory parameters included erythrocyte sedimentation rate (ESR) of 47 mm/hr and peak troponin of 0.26 ng/mL. Transthoracic echocardiogram (TTE) revealed preserved ejection fraction with no segmental wall motion abnormalities; however, it showed moderate pericardial effusion without tamponade physiology. We hypothesize that this myopericarditis could be due to HCTZ allergic reaction after all other common etiologies have been ruled out. There is a scarcity of the literature regarding HCTZ as an etiology for pericardial disease, with only one case reported as presumed hydrochlorothiazide-induced pericardial effusion. Management involves discontinuation of HCTZ and starting anti-inflammatory therapy.